EXERCISE IS MEDICINE: PRIMARY CARE COUNSELING ON AEROBIC FITNESS AND MUSCLE STRENGTHENING - Crump, Casey (J Am Board Fam Med, 2019)
Patient counseling on physical fitness remains underutilized in primary care, despite its clinical and cost effectiveness. Most counseling interventions have focused on aerobic activity and neglected another vital component of physical fitness—muscle strengthening—which has recently been shown to be independently protective against cardiometabolic diseases and premature mortality. This article reviews the latest scientific evidence and makes recommendations toward a more comprehensive approach for promoting physical fitness in primary care. Given the high prevalence and wide-ranging health impacts of physical inactivity, counseling on physical fitness should be a standard part of wellness promotion and disease prevention and treatment for all patients. Interventions that include muscle strengthening will have a significantly greater impact on health outcomes than those focused on aerobic fitness alone. Counseling to promote both aerobic fitness and muscle strengthening is indicated for all patients, irrespective of body weight, and should begin early in life and continue across the life course.